2012
DOI: 10.1371/journal.pone.0029054
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Accumulation of Polymorphonuclear Neutrophils in the Corpus luteum during Prostaglandin F2α-Induced Luteolysis in the Cow

Abstract: Prostaglandin F2α (PGF2α) induces luteolysis within a few days in cows, and immune cells increase in number in the regressing corpus luteum (CL), implying that luteolysis is an inflammatory-like immune response. We investigated the rapid change in polymorphonuclear neutrophil (PMN) numbers in response to PGF2α administration as the first cells recruited to inflammatory sites, together with mRNA of interleukin-8 (IL-8: neutrophil chemoattractant) and P-selectin (leukocyte adhesion molecule) in the bovine CL. CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 49 publications
(76 reference statements)
8
23
0
Order By: Relevance
“…Both pathways stimulate the secretion of pro-inflammatory cytokines. Similarly, proinflammatory gene expression increases during regression of the CL (Atli et al, 2012;Shirasuna et al, 2012). Therefore, an increase in both TLR2 and TLR4 mRNA and protein levels in rCL in the present study may indicate roles of TLR signaling in the proinflammatory cytokine-mediated regressing mechanism in bovine CL.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Both pathways stimulate the secretion of pro-inflammatory cytokines. Similarly, proinflammatory gene expression increases during regression of the CL (Atli et al, 2012;Shirasuna et al, 2012). Therefore, an increase in both TLR2 and TLR4 mRNA and protein levels in rCL in the present study may indicate roles of TLR signaling in the proinflammatory cytokine-mediated regressing mechanism in bovine CL.…”
Section: Discussionsupporting
confidence: 56%
“…For example, despite the fact that the PGF 2α receptor was only detected in large luteal cells where the first luteolytic signal was expected to start (Mamluk et al, 1998), our previous studies have shown that luteolytic induction occurs in endothelial cells earlier than in luteal cells (Atli et al, 2011;Atli et al, 2012). Although the role of immune cells in the CL was previously thought to be in phagocytosis following luteolysis (reviewed by Pate and Landis Keyes, 2001), the immune cell population and chemokines in the CL are affected during functional luteolysis in the early response to PGF 2α (Shirasuna et al, 2012). Moreover, immune system roles were demonstrated in the dCL in a previous study (Poole and Pate 2012).…”
Section: Introductionmentioning
confidence: 97%
“…During the past decade, treatment with a PGF analog has become a model for study of the control of progesterone concentration and luteal blood flow during luteolysis in cattle [63,[66][67][68]. For example, the model has been used to demonstrate that polymorphonuclear neutrophils accumulate in the corpus luteum within 5 min after treatment [66] and that nitric oxide is produced in the corpus luteum as a function of PGF [68].…”
Section: Progesterone Circulatory Dynamicsmentioning
confidence: 99%
“…For example, the model has been used to demonstrate that polymorphonuclear neutrophils accumulate in the corpus luteum within 5 min after treatment [66] and that nitric oxide is produced in the corpus luteum as a function of PGF [68]. However, examination of the published progesterone profiles [66,68] indicates to us that the model was associated with a nonphysiological increase in progesterone. Hypotheses were tested during the nonphysiological progesterone increase and related by interpretation to spontaneous physiological mechanisms.…”
Section: Progesterone Circulatory Dynamicsmentioning
confidence: 99%
“…Both SELP and SELL are significantly upregulated in endometrial cells stimulated with the bacterial product lipopolysaccharide (LPS) (Oguejiofor et al, 2015). SELP is also crucial for the migration of PMN into the bovine corpus luteum during luteolysis (Shirasuna et al, 2012). Persistent corpora lutea are commonly present in cows with uterine infection (Opsomer et al, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%